Legislating for the Periphery: A Policy Mapping of Republic Acts Exclusive to Misamis Occidental and Their Local Implications - Gerald Besto (Konsultan Surya Buanan, 2026)
This study presents a comprehensive desk research on Republic Acts (RAs) that are intended and exclusive for Misamis Occidental, to map legislative measures, examining their implications, and formulating recommendations for future policy directions. While national policies are designed to address broad developmental needs, certain provinces, such as Misamis Occidental, benefit from laws specifically tailored to their socio-economic, environmental, and cultural contexts. The methodology employed involves a systematic review of official government databases, legislative archives, and secondary sources to identify RAs explicitly referencing Misamis Occidental. These were then categorized by policy domains such as education, health, environment, infrastructure, and cultural heritage. Findings reveal that several laws have been enacted to establish state universities and colleges, declare protected areas, create economic and agricultural support systems, and enhance healthcare delivery within the province. For example, legislation on Mt. Malindang as a Natural Park underscores environmental conservation, while the creation of Northwestern Mindanao State College of Science and Technology highlights investments in higher education. The study also found that while these laws address sectoral needs, gaps remain in areas such as digital innovation, disaster resilience, and livelihood diversification. The discussion emphasizes that localized legislation plays a vital role in aligning national development goals with provincial realities. However, to maximize their impact, proper implementation, sustained funding, and participatory governance are crucial. Recommendations include institutionalizing periodic policy reviews, expanding legislative coverage to underrepresented sectors, and adopting inclusive frameworks that respond to emerging socio-economic challenges in Misamis Occidental.